UML - Conner, Nancy, 1961-; Safari eBooks ([S.l.] : Virtual Training Company, 2003)
"UML is a standard, visual modeling language that comes into play in all stages of the software development life cycle: modeling business processes, conceptualizing system functions, visualizing and documenting software artifacts, developing object-oriented software. In other words, UML is a language that allows the writing of a software system's blueprint in a way that can be easily understood by various stakeholders, including business analysts, project managers, system and database architects, etc. This introduction, by VTC author and corporate trainer Nancy Conner, covers UML basics and goes into detail about the most common kinds of UML diagrams. To begin learning, simply click the links" --Resource description page.
Title from resource description page (viewed Jul. 25, 2011).
Presenter, Nancy Conner.
Keywords: Computer software -- Development; Software architecture; Computer simulation; Electronic books